Results for retarded nonlinear integral inequalities with mixed powers and their applications to delay integro-differential equations - Shakoor А.; Samar, M.; Athar, T.; Saddique, M. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.9 We present new retarded nonlinear integral inequalities with mixеd powers. The obtained inequalities can be used to study the boundedness and global existence of the solutions of integro-differential equation with delay and Volterra-type integral equation with delay. These inequalities extend some results available in the literature. Finally, we present two examples to demonstrate the usefulness of our main results.